Comparative study between the effect of dexmedetomidine and lidocaine infusion on intraoperative analgesic requirement and hemodynamics during craniotomy - Ghosal, Agnimitra; Debnath, Tanay; Chakraborty, Soma; Das, Debojyoti; Laha, Arpita; Mandal, Mohanchandra; Acharjee, Amita (Asian Journal of Medical Sciences, 2024)
Background: Nowadays, anesthesiologists are evaluating several analgesic adjuncts to minimize opioid use during craniotomy. Some studies have evaluated the analgesic-sparing effect of intravenous infusion of dexmedetomidine and lidocaine on intraoperative hemodynamics and post-operative analgesia. There is a paucity of studies focussing on the intraoperative analgesic requirement. Aims and Objectives: The present study compared dexmedetomidine and lidocaine infusion primarily for their effects on intraoperative fentanyl requirements during craniotomy. Materials and Methods: This study was done on 70 patients aged 18–80 years, the American Society of Anesthesiologists physical status I–II, having Glasgow Coma Scale 15, undergoing craniotomies. Patients were randomly allocated to receive either dexmedetomidine (group A, n=35) at a dose of 0.6 mcg/kg bolus over 10 min followed by 0.6 mcg/kg/h infusion or lidocaine (group B, n=35) at a dose of 1.5 mg/kg bolus over 10 min, followed by 1.5 mg/kg/h infusion till the end of skin suture, respectively. Study drugs were started 10 min before the start of surgery. Intraoperative total fentanyl and propofol consumption, intraoperative hemodynamics, recovery from hypnosis, and time to extubation were recorded. Results: The use of dexmedetomidine resulted in considerably less total fentanyl requirement (245.1 vs. 300.7 mcg, P<0.0001) and total propofol requirement (172.7 vs. 236.7 mg, P<0.0001) compared with lidocaine. Comparatively better hemodynamics were observed with the use of dexmedetomidine at all the points of observation. Conclusion: Dexmedetomidine as an analgesic adjunct can be a better alternative to lidocaine in terms of reduced fentanyl consumption, reduced propofol use and favorable hemodynamics, and early recovery from anesthesia.